ANALISIS PERKEMBANGAN, KONTRIBUSI DAN EFEKTIVITAS PAJAK PENERANGAN JALAN DI KABUPATEN SAROLANGUN TAHUN 2011-2013 - Dian Utama Saroja (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2016)
This study aims to (1) analyze the development of street lighting tax in Sarolangun Regency, (2) analyze the contribution of street lighting tax revenue in Sarolangun Regency (3) analyze the effectiveness of street lighting tax in Sarolangun Regency. The methods used to answer the problems in this research are developmental analysis, effectiveness analysis, and contribution analysis. The results of the study show that street lighting tax revenues in Sarolangun Regency during 2011-2013 experienced an average growth of 24.91%. The amount of street lighting tax contribution to PAD in Sarolangun Regency in 2011-2013 was less contributing with an average of 13.61%. While its effectiveness during 2011-2013 averaged 126.66% (very effective),